Komitmen Politik Pemerintah Dalam Pengelolaan Sampah Di Kecamatan Long Bagun - Nobertus Ngande; Yulita Tipung; Jauchar B (Bajang Institute, 2026)
Effective waste management is vital for sustainable development, yet its success in remote regions depends largely on the political will of local governments. This study analyzes the government’s political commitment (political will) in waste management in Long Bagun District, Mahakam Ulu Regency, Indonesia. Using a descriptive qualitative approach, data were obtained from document analysis, including the 2024 Waste Management Balance Report (SIPSN) and Mahakam Ulu Regent Regulation Number 30 of 2019 on the Regional Policy and Strategy (Jakstrada) for Waste Management. Findings indicate that although regulatory frameworks are in place, implementation has not fully demonstrated strong political will. Indicators such as policy clarity, institutional capacity, resource allocation, political leadership, and program sustainability remain weak. These limitations highlight a gap between policy formulation and practice, aggravated by challenges typical of 3T (disadvantaged, frontier, and outermost) areas, including limited infrastructure, human resources, and community engagement.The study recommends strengthening institutional structures, increasing budget allocations, and enhancing community participation to translate policy into tangible and sustainable waste management outcomes. Addressing these factors will enable local governments to bridge the gap between regulation and reality, fostering environmental sustainability in remote regions such as Long Bagun